Seismic performance analysis of viscous damping outrigger in super high‐rise buildings. (27th July 2018) - Ding, Jiemin; Wang, Shiyu; Wu, Honglei
Summary: This paper introduces a seismic energy dissipation technology—viscous damping outrigger (VDO)—which is composed of outrigger truss and viscous damper. The viscous damper is set up vertically at the end of outrigger truss, which is an innovative and high‐efficiency arrangement. VDO can fully utilize the characteristic of structural lateral deformation of super high‐rise buildings to increase the efficiency of viscous dampers for enhancing structural security, improving seismic performance, and reducing construction expenditure. In this paper, working principle and seismic energy dissipating mechanism of VDO are explained firstly. Then, the influence of viscous damper parameters on energy dissipation efficiency is studied. Next, the optimal position of VDO in a super high‐rise building is analyzed in detail. Lastly, the application of VDO in structural seismic design of a super high‐rise building in China will be clearly verified based on their feasibility, economy, and safety.